2018
DOI: 10.3390/nu10020171
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Intakes, Food Sources and Excretions of Phosphorus and Calcium in Three German Study Collectives

Abstract: Phosphorus intake in Europe is far above recommendations. We present baseline data from three human intervention studies between 2006 and 2014 regarding intake and excretion of phosphorus and calcium. All subjects documented their nutritional habits in weighed dietary records. Fasting blood samples were drawn, and feces and urine were quantitatively collected. Dietary phosphorus intake was estimated based on weighed dietary records and urine phosphorus excretions. Food sources were identified by allocation to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
5
17
0
Order By: Relevance
“…Therefore, 24 h measurements of urinary phosphate have been considered a reliable biomarker for dietary phosphate absorption. Several studies have confirmed this in patients with preserved kidney function [16,43,44]. In our study we compared CBA phosphate uptake with DA phosphate intake and found that on average CBA phosphate uptake was higher.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, 24 h measurements of urinary phosphate have been considered a reliable biomarker for dietary phosphate absorption. Several studies have confirmed this in patients with preserved kidney function [16,43,44]. In our study we compared CBA phosphate uptake with DA phosphate intake and found that on average CBA phosphate uptake was higher.…”
Section: Discussionsupporting
confidence: 75%
“…In the European Union and Switzerland, the use of PPi as food additive E450 is not restricted, and PPi is found in high concentrations in products such as canned meat, fish, and bakery products . Although the dietary intake of naturally occurring (polyoxo)phosphates does not represent a risk for healthy people, the increasing use of phosphate salts as food additives exposes risks to people with renal disorders and cardiovascular diseases . For this reason, the restriction of dietary phosphate is recommended for patients with chronic renal failures for many years …”
Section: Introductionmentioning
confidence: 99%
“…Trautvetter et al (2018) showed that microbiota and faecal short-chain fatty acids (SCFA) were modulated by phosphate supplementation [ 13 ]; however, it was also shown that calcium metabolism was impaired by a high-phosphate diet [ 20 ]. Such effects of phosphate supplementation are of particular interest, since the phosphorus intake of Western societies is far above the recommendation, not least due to the usage of phosphate additives in food production [ 6 , 21 ].…”
Section: Introductionmentioning
confidence: 99%